FILSAFAT PROGRESIVISME JOHN DEWEY DALAM SISTEM PENDIDIKAN HOMESCHOOLING - Zianda Alfarizzaki, Muhammad (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study examines the relevance of John Dewey’s philosophy of progressivism in the context of homeschooling education in Indonesia. Using a qualitative approach and multi-case study method, this research combines conceptual analysis of Dewey’s key works, such as Democracy and Education and Experience and Education, with empirical data from five homeschooling families across different regions. The focus is on how Dewey’s principles of “learning by doing” and “education as life” are adopted and adapted in home-based education practices. The findings reveal that progressive homeschooling creates a democratic, flexible, and contextualized learning environment, where parents act as facilitators rather than authoritarian instructors. Children are given autonomy to choose subjects and learning methods aligned with their interests and learning styles, while daily experiences and community settings function as dynamic learning environments. The study also highlights the importance of social interaction, critical reflection, and experience-based evaluation in progressive homeschooling models. Despite challenges such as social isolation and limited resource access, this model remains relevant as an inclusive, participatory, and adaptive educational alternative in the face of rapid societal change. The study recommends strengthening homeschooling community networks and providing pedagogical training for parents as strategic efforts to support the growth of non-formal progressive education in Indonesia.